2008
DOI: 10.1111/j.1365-2249.2008.03859.x
|View full text |Cite
|
Sign up to set email alerts
|

Implications for a role of interleukin-23 in the pathogenesis of chronic gastritis and of peptic ulcer disease

Abstract: SummaryThe present study aimed to investigate the role of gastric mucosa for the secretion of interleukin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
4
12
0
Order By: Relevance
“…IL‐23 and IL‐1ß levels in the supernatants of the samples of gastric mucosa, taken from patients with duodenal ulcers, with gastric ulcers and with chronic gastritis, were higher among the H. pylori ‐positive patients, as compared with the H. pylori ‐negative patients . In a recent study, increased IL‐23, IL‐6, and TGF‐β cytokines were observed in the culture‐containing macrophage cells stimulated with H. pylori antigen, followed by the activation of Th17, and the secretion of IL‐17 .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…IL‐23 and IL‐1ß levels in the supernatants of the samples of gastric mucosa, taken from patients with duodenal ulcers, with gastric ulcers and with chronic gastritis, were higher among the H. pylori ‐positive patients, as compared with the H. pylori ‐negative patients . In a recent study, increased IL‐23, IL‐6, and TGF‐β cytokines were observed in the culture‐containing macrophage cells stimulated with H. pylori antigen, followed by the activation of Th17, and the secretion of IL‐17 .…”
Section: Discussionsupporting
confidence: 72%
“…In addition to evaluating the serum levels of IL-17A, IL-21, IL-22, IL-23, and TGF-b, and their differences in the above-mentioned patients, we also evaluated the levels of these cytokines in the same groups of patients through stimulating the PBMCs by H. pylori antigen, PHA, or anti-CD3/CD28. IL-23 and IL-1ß levels in the supernatants of the samples of gastric mucosa, taken from patients with duodenal ulcers, with gastric ulcers and with chronic gastritis, were higher among the H. pylori -positive patients, as compared with the H. pylori -negative patients [35]. In a recent study, increased IL-23, IL-6, and TGF-b cytokines were observed in the culture-containing macrophage cells stimulated with H. pylori antigen, followed by the activation of Th17, and the secretion of IL-17 [46].…”
Section: Discussionmentioning
confidence: 85%
“…23 Similarly, in the current study we observed in- Knowing the fact that, naïve CD4-positive T-cell differentiation into Th22 is regulated by IL6 and TNFα, and promoted by IL1β. Therefore, overactivity of these cells and a shift in favor of pro-inflammatory cytokines may lead to gastric ulcers.…”
Section: In Vitro Cytokine Production By Pbmcs Stimulated With H Psupporting
confidence: 80%
“…Koussoulas and Shamsdin determinedthat IL-23 might play a critical role in the process of inflammation and contribution to gastritis 19,23. Koussoulas and Shamsdin determinedthat IL-23 might play a critical role in the process of inflammation and contribution to gastritis 19,23.…”
mentioning
confidence: 99%
“…However, positive correlations were found between levels of IL-23 and the degree of infiltration of neutrophils and monocytes in patients with H. pylori infection, and the kinetics of IL-23 expression correlates with those of IL-1β (Koussoulas et al, 2009). …”
Section: Introductionmentioning
confidence: 99%